2021
DOI: 10.3390/plants10112305
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Metabolic Plant Responses toward Polycyclic Aromatic Hydrocarbons and Heavy Metals Present in Atmospheric Pollution

Abstract: Heavy metals (HMs) and polycyclic aromatic hydrocarbons (PAHs) are toxic components of atmospheric particles. These pollutants induce a wide variety of responses in plants, leading to tolerance or toxicity. Their effects on plants depend on many different environmental conditions, not only the type and concentration of contaminant, temperature or soil pH, but also on the physiological or genetic status of the plant. The main detoxification process in plants is the accumulation of the contaminant in vacuoles or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 248 publications
(319 reference statements)
0
33
0
1
Order By: Relevance
“…Sugar and sugar derivative synthesis/accumulation may contribute to satisfy the increasing energy demand required to tolerate the adverse stress conditions and/or, acting as osmolytes, to protect cells and sustain a minimal osmotic balance under water stress conditions determined not only by salinity but also by pollution with high molecular weight polycyclic aromatic hydrocarbons (PAH) ( 29 , 30 ). In this regard, Molina and Segura ( 32 ) reported that sugar metabolisms are activated by the presence of PAH with a consequential increase of glucose, mannose, galactose, raffinose, galactinol, melibiose, and sucrose contents in plant tissues. A decrease in fruit quality and sugar content was, instead, reported in peppers grown in hydroponic systems under a glasshouse exposed to 5 mS/cm salinity possibly determined by the enhancement of respiration rate of stressed fruits ( 33 , 34 ), confirming that the responses to salinity stress are species specific, or even variety dependent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugar and sugar derivative synthesis/accumulation may contribute to satisfy the increasing energy demand required to tolerate the adverse stress conditions and/or, acting as osmolytes, to protect cells and sustain a minimal osmotic balance under water stress conditions determined not only by salinity but also by pollution with high molecular weight polycyclic aromatic hydrocarbons (PAH) ( 29 , 30 ). In this regard, Molina and Segura ( 32 ) reported that sugar metabolisms are activated by the presence of PAH with a consequential increase of glucose, mannose, galactose, raffinose, galactinol, melibiose, and sucrose contents in plant tissues. A decrease in fruit quality and sugar content was, instead, reported in peppers grown in hydroponic systems under a glasshouse exposed to 5 mS/cm salinity possibly determined by the enhancement of respiration rate of stressed fruits ( 33 , 34 ), confirming that the responses to salinity stress are species specific, or even variety dependent.…”
Section: Resultsmentioning
confidence: 99%
“…The observed increase is possibly related to an active accumulation of ions and organic acids produced by the plant under stress conditions. Alterations in the relative concentrations of tricarboxylic acid cycle intermediates, resulting in increased citrate and malate levels but α-ketoglutarate, fumarate, oxaloacetate, pyruvate, and succinate decrease, were reported in response to PAH as a consequence of the overexpression or downregulation of the enzymes of the Krebs cycle and of the mitochondrial respiratory chain ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In extreme cases, the low oxygen content can contribute to the formation of dead zones, which can cause water bodies to become uninhabitable for their flora and fauna (Trevors & Saier, 2010). Plants in surrounding lake ecosystems are also susceptible, as PAHs have been demonstrated to have negative effects on plant germination, biomass yield, and growth (Molina & Segura, 2021). This may be caused by mechanical disruption of cellular membranes in the plant, which impairs its capacity to retain water and take up nutrients from the soil (Molina & Segura, 2021).…”
Section: Impact Of Fuel Spills From a One Health Perspectivementioning
confidence: 99%
“…Plants in surrounding lake ecosystems are also susceptible, as PAHs have been demonstrated to have negative effects on plant germination, biomass yield, and growth (Molina & Segura, 2021). This may be caused by mechanical disruption of cellular membranes in the plant, which impairs its capacity to retain water and take up nutrients from the soil (Molina & Segura, 2021). Therefore, due to the great interconnectivity between humans, non-human animals, and the environment, a One Health approach is essential when tackling fuel spillage in freshwater lakes.…”
Section: Impact Of Fuel Spills From a One Health Perspectivementioning
confidence: 99%